E-beam lithography exposure conditions for the fabrication of RGB filter based on metal/dielectric subwavelength grating. (August 2016) - Fomchenkov, S A; Butt, M A; Podlipnov, V V; Poletaev, S D; Skidanov, R V; Kazanskiy, N L
Abstract: The main idea of this work was to determine the optimized parameters of E-beam lithography to obtain metal grating over dielectric thin film. This combination of metal/dielectric can provide high transmission spectrum of RGB colors. Different electric flux densities were used during E-beam writing and the best resolution and symmetric periodicity was obtained at 53 μC/cm 2 dose.